Extrapyramidal signs and Alzheimer's disease prognosis in a multiethnic, community‐based sample of demented elders. Issue 9 (12th March 2021) - Kociolek, Anton J.; Fernandez, Kayri K.; Jin, Zhezhen; Cosentino, Stephanie; Zhu, Carolyn W.; Gu, Yian; Stern, Yaakov
Abstract: Introduction: Extrapyramidal signs (EPS) are a common feature of Alzheimer's disease associated with worse outcomes in observational studies of dementia. Less research has been conducted on ethnic minority and non‐clinic‐based populations. Methods: One hundred and forty‐two multiethnic community‐dwelling participants with dementia were selected. Adjusted Cox models were fitted for mortality, cognitive (Mini Mental State Examination ≤10), functional (Blessed Dementia Rating Scale ≥10), and dependency (needs full‐time care) endpoints with baseline EPS as predictor. Results: Thirty‐seven participants (26.06%) had EPS at baseline. EPS predicted more rapid time to death (hazard ratio [HR] = 2.76, 95% confidence interval [CI] = 1.49, 5.42), and functional endpoint (HR = 3.88, 95% CI = 1.75, 8.62) but not cognitive and dependency endpoints. No evidence of interaction by ethnicity, age, sex, education, or apolipoprotein E ε4 polymorphism was found. Discussion: Our results partially confirm previous studies on predominantly White, clinic‐based samples. Further research is needed to better understand the etiological role of EPS in AD.